People's Republic of China Financial Sector Assessment Program : IAIS Insurance Core Principles - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
Insurance companies in China are closely supervised and generally subjected to appropriate regulation. The China Insurance Regulatory Commission (CIRC) employs a rules based framework and has achieved a high level of regulatory compliance from supervised companies. This assessment of the People's Republic of China's compliance with International Association of Insurance Supervisors (IAIS) Insurance Core Principles (ICP) was carried out as part of the 2010 Financial Sector Assessment Program (FSAP). The CIRC has principal responsibility over insurance regulation in China and conducts its duties through its headquarters in Beijing and 35 regional branches, the insurance bureaus. Insurance supervision is not limited to the CIRC, as it is affected by high level regulations issued by the state council.